Technical And Safety Assessment Of Grade Separation At Jpl 193 Km 182+055 Between Haurpugur And Cicalengka - Mariana Diah Puspitasari; Adam Dzaki Ardiansyah; Rusman Prihatanto; M. Adib Kurniawan; Septiana Widi Astuti (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2026)
Level crossings are critical points in transport systems because they create direct conflicts between railway and road traffic, especially when technical safety requirements are not fulfilled. This study evaluates the condition of level crossing JPL 193 KM 182+055 between Haurpugur and Cicalengka Stations, focusing on crossing geometry, traffic loading, and the need for infrastructure upgrading. The study employed a descriptive quantitative approach through field observation, elevation measurement, skilu analysis, and traffic load calculations using Passing Tonnage for railway traffic and Equivalent Single Axle Load (ESAL) for road traffic. The results show that the elevation deviation between the road surface and rail head reached 60–70 mm, exceeding the allowable tolerance, while skilu values remained within acceptable limits. Railway traffic load reached 116,261,318 tons/year and was classified as railway class II, while road traffic loading reached 1,735,258 ESAL. The crossing also failed to comply with several key requirements for maintaining an at-grade crossing, including train speed, headway, road class, and crossing surface tolerance. Based on these findings, conversion into a grade-separated crossing is recommended through the construction of a flyover with a concrete girder bridge system and bore pile foundation. This study provides a technical basis for decision-making to improve transport safety and infrastructure performance at high-risk crossings.